EVALUATION OF THE TECHNOLOGICAL PRINCIPLES AND QUALITY INDICATORS OF ECO-FRIENDLY BIOLEATHER-LIKE MATERIAL PRODUCTION BASED ON FRUIT PEEL WASTE - S.N.Obloberdiyev; F.Sh.G‘ulomova; G.Sh.Korabekova; M.J.Bekmurodova; Sh.E.Ulashova; Z.A.Madusmonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This study evaluates the technological principles of producing an eco-friendly bioleather-like material based on fruit peel waste. Fruit peel waste was used as a natural raw material source due to its cellulose, pectin, and fiber content. The obtained biocomposite material was assessed according to its appearance, flexibility, surface structure, thickness, strength, and biodegradability. The results indicate that fruit peel waste can be effectively used to develop sustainable, low-cost, and environmentally safe bioleather-like materials.